Tinjauan Yuridis Pembangunan Waduk Lambo di Atas Tanah Ulayat di Desa Rendubutowe Kabupaten Nagekeo - Caecelia Yasintha Putri Daki; Yossie M. Y. Jacob; Rini Marselin Kaesmetan (Pusat Riset dan Inovasi Nasional, 2025)
This research is a research that aims to find out and analyze the construction of lambo reservoirs on customary land in Rendubutowe Village, Nagekeo Regency. This research is an empirical research using primary and secondary data collected using interview techniques and literature studies and analyzed in a qualitative descriptive manner. The results of the study show that (1) the stages of fulfilling the rights of the community related to the construction of the Lambo Reservoir have been carried out based on the applicable laws and regulations (2) the inhibiting factors in the process of fulfilling the rights of the community are legal and regulatory constraints, social and cultural constraints, economic and administrative constraints.